Exploiting the Potential of Supported Magnetic Nanomaterials as Fenton-Like Catalysts for Environmental Applications - Jorge González-Rodríguez (MDPI AG, 2021)
In recent years, the application of magnetic nanoparticles as alternative catalysts to conventional Fenton processes has been investigated for the removal of emerging pollutants in wastewater. While this type of catalyst reduces the release of iron hydroxides with the treated effluent, it also presents certain disadvantages, such as slower reaction kinetics associated with the availability of iron and mass transfer limitations. To overcome these drawbacks, the functionalization of the nanocatalyst surface through the addition of coatings such as polyacrylic acid (PAA) and their immobilization on a mesoporous silica matrix (SBA15) can be factors that improve the dispersion and stability of the nanoparticles. Under these premises, the performance of the nanoparticle coating and nanoparticle-mesoporous matrix binomials in the degradation of dyes as examples of recalcitrant compounds were evaluated. Based on the outcomes of dye degradation by the different functionalized nanocatalysts and nanocomposites, the nanoparticles embedded in a mesoporous matrix were applied for the removal of estrogens (E1, E2, EE2), accomplishing high removal percentages (above 90%) after the optimization of the operational variables. With the feasibility of their recovery in mind, the nanostructured materials represented a significant advantage as their magnetic character allows their separation for reuse in different successive sequential batch cycles.